CENTRIFUGAL CLUTCH DESIGN FOR VARIOUS APPLICATIONS - sehgal, Karan; pratap, Anuj; kuhar, Ravi (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The centrifugal clutch offers many advantages in motor and engine drive applications. Utilizing the centrifugal clutch enables the selection of normal torque motors for running loads rather than the selection of high torque motors for starting loads. The aim of this project is to be describing the torque carrying capacity at different speed which using in transmitting power. The entire work based on conventional design with Ferro do lining, driving shaft, spring, shoe, spider, cover plate, driven shaft. Compliant clutch is made from polypropylene material and there is no anyone connecting parts. it has rigid body design since revolute joints are replaced by flexible segment. The potential energy store in flexible segment can replace springs and reduction in revolute joints reduces problem with backlash and wear. A mechanism is evaluated and synthesized specific force-deflection relationship. In many applications, compliant mechanism can maintain or even improve performance relative to conventional rigid body designs. It is cost benefitted. Also conventional clutch is expensive rather than compliant clutch.